KINERJA PENGAWAS DALAM MENINGKATKAN PROFESIONALISME GURU PAI DI KOTA PALU - Retoliah Retoliah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2014)
This research regarding the performance of Supervisor in improving the professionalism of Islamic Education teachers in Palu. The main issue discussed was how the performance of the islamic Education supervisor in Palu and their efforts in improving the professionalism of Islamic Education teachers in Palu. This study uses descriptive qualitative approach to collect the data through observation, interviews and documentation and to analysis the data. The results showed that the performance of the Islamic Education Supervisor in Palu in the preparation of supervision program of Prota, Prosem and RKA is successful. The Performance of Islamic Education Supervisor in the implementation of the program is generally managed in accordance with their duties Their duties are to monitor, to inspect, to supervise, to assess and to provide guidance to Islamic Education teachers based on findings during supervision in the form of individual and group coaching. The Supervisor efforts in improving the professionalism of Islamic Education teachers done in two ways: directly and indirectly. Firstly, provide guidance directly based on the problems faced by teachers in schools and secondly, provide guidance indirectly by collaborating with the Ministry of Religious Pendis Palu in improving the quality of teachers through giving training